2017
DOI: 10.1002/ejhf.886
|View full text |Cite
|
Sign up to set email alerts
|

Late graft failure in heart transplant recipients: incidence, risk factors and clinical outcomes

Abstract: Late graft failure is frequent after heart transplantation, as it is associated with poor outcomes. Rejection and cardiac allograft vasculopathy are the most frequent underlying causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 23 publications
(35 reference statements)
3
43
0
Order By: Relevance
“…Cardiac allograft vasculopathy affects 40% of patients after 5 years and is by far the leading cause of late graft failure . While treatment with statins and tight risk factor control are key, it has become clear that different immunosuppressive regimens are associated with different risks of CAV development.…”
Section: Main Challenges and Emerging Solutionsmentioning
confidence: 99%
“…Cardiac allograft vasculopathy affects 40% of patients after 5 years and is by far the leading cause of late graft failure . While treatment with statins and tight risk factor control are key, it has become clear that different immunosuppressive regimens are associated with different risks of CAV development.…”
Section: Main Challenges and Emerging Solutionsmentioning
confidence: 99%
“…For example, in an analysis of the ISHLT Registry, we observed that younger patients were at considerably greater risk for death from acute rejection, CAV and graft failure, potentially implying inadequate immunosuppression, whereas older patients had greater risk for death from infection and malignancy, consequences of immunosuppression . The data from A Coruña suggest we should also be vigilant about rejection and by extension adequate immunosuppression in the long term; however, data from the ISHLT suggest that malignancy, a consequence of immunosuppression, is the most common cause of death beyond 5 years post‐HTx . There is clearly a great need for additional studies of the relative risks for different post‐HTx outcomes according to time post‐transplant and individual patient characteristics.…”
mentioning
confidence: 92%
“…However, data from the International Society for Heart and Lung Transplantation (ISHLT) Registry suggest that long‐term adult post‐HTx outcomes have not improved appreciably since reporting to this worldwide registry begun in the early 1980s and that mortality at 13 years is >50% . In this issue of the journal, the large HTx group from A Coruña, Spain, report specifically on late graft failure in 547 HTx recipients aged 16 years or older . The study is laudable for its large sample size and detailed analysis of both graft failure and its predictors, and outcomes post‐graft failure and their predictors.…”
mentioning
confidence: 99%
See 2 more Smart Citations